Anemia among pregnant women in internally displaced camps in Mogadishu, Somalia: a cross-sectional study on prevalence, severity and associated risk factors - Ramla Hussein Ahmed; Asha Abdirahman Yussuf; Asma Abdikarin Ali; Sowdo Nuur Iyow; Maryan Abdulahi; Lul Mohamud Mohamed; Mohamed Hayir Tahlil Mohamud (BMC, 2021)
Abstract Background Anemia in pregnancy is a serious global public health problem in most developing countries and a major cause of maternal morbidity and mortality. Somalia which already had very high maternal mortality ratio of 829 per 100,000 live births, pregnant women in internally displaced camps (IDPs) remain at most exposed. The aim of the study was to determine the prevalence, severity and associated risk factors of anemia among pregnant women in internally displaced camps in Mogadishu, Somalia. Methods A community based cross-sectional study was conducted among 383 households in the most IDP settled districts in Mogadishu. Every pregnant mother in these sampled households who was voluntarily consented was targeted. A sample of blood was also taken by pricking the fingertip and inserted into hemoglobin meter. Those with Hb < 11 g/dl from hemoglobin meter had been taken another sample of 3 cc blood and put into EDTA tube for CBC analysis to identify the type of anemia. Data on risk factors were collected using structured pretested questionnaire via an interview. Collected data was coded and entered in SPSS- Version 22 for analysis. Descriptive analysis, bivariate chi-square and multivariate logistic regression were done. Results The overall prevalence of anemia among study participants was 44.4% (95%CI: 39.5-49.3%), where severe and moderate anemia were 11.8 and 47.0% respectively. In addition all anaemic cases were microcytic hypochromic anemia. Young maternal age, low Family income, fewer/zero parity, being at third or second trimesters, lack of ANC attendance during pregnancy, lack of iron supplementation during pregnancy, taking tea immediately after meal during pregnancy, lower/zero frequency of daily meat and vegetables consumption during pregnancy were associated risk factors of anemia. Conclusion The anemia prevalence from this study was severe public health problem. Several factors were found to be associated with anemia during pregnancy. Measures has to be taken to curb the problem by including them mass iron supplementation and health education towards identified risk factors.